Effect of an herbal extract of Sideritis scardica and B-vitamins on cognitive performance under stress: a pilot study - Isabel Behrendt; Inga Schneider; Jan Philipp Schuchardt; Norman Bitterlich; Andreas Hahn (International Journal of Phytomedicine, 2016)
Chronic stress can impair cognitive functions including learning and memory. The current study investigated the reduction of (mental) stress and improvement of stress tolerance in 64 healthy men and women after six weeks intake of a dietary supplement containing an extract of Sideritis scardica and selected B-vitamins. Mental performance and visual attention were measured by Trail-Making Test (TMT) and Colour-Word-Test (CWT) before/after an acute stress stimulus (noise, CW-Interference). TMT improved upon product intake. The CWT reaction time accelerated upon product intake in situations of CW-Congruence (overall) (p=0.014), CW-conflict (overall) (p=0.024), CW-conflict (with noise) (p=0.001), CW-Congruence (without noise) (p=0.004) and CW-conflict (without noise) (p=0.017). CWT-changes upon product intake, differentiated for noise and CW-interference, showed (i) a bisection of CW-interference-related impairment of the reaction time in the presence of noise from 27 ms to 13.5 ms, (ii) a bisection of noise-related impairment of the reaction time in the presence of CW-conflict from 34 ms to 17 ms, (iii) an improvement of the impairment of the reaction time due to combined stress (noise plus CW-conflict) by 14.5 ms from 66 ms to 51.5 ms, (iv) despite of the improvement of the reaction time, no increase of the error rate. Safety blood parameters and the reporting of no adverse events argue for the product’s safety. These results may be relevant for persons solving cognitive tasks under conflict and/or noise (e.g. open-plan offices or car-driving) and support that the tested product alleviates stress-induced impairment of executive functioning (working memory, cognitive flexibility, controlled behavioural inhibition).